Інновації як інструмент управління ризиками та забезпечення конкурентних переваг підприємства - Тебенко, Віта Миколаївна; Tebenko, Vita; Лисак, Оксана Іванівна; Lysak, Oksana; Болтянська, Лариса Олексіївна; Boltianska, Larysa (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджено роль інновацій як інструмента управління ризиками та забезпечення конкурентних переваг промислових підприємств України в умовах невизначеності та воєнних викликів. На основі статистичних даних за 2020–2024 рр. проаналізовано динаміку інноваційної активності, обсяги реалізації інноваційної продукції та структуру фінансування інновацій. Встановлено, що після падіння інноваційної активності у 2022–2023 рр. підприємства демонструють відновлення й посилення інноваційної діяльності. Виявлено зростання обсягів інноваційної продукції та розширення джерел її фінансування, зокрема коштів інвесторів. Доведено, що інновації є ключовим фактором формування стійкості та конкурентоспроможності промислових підприємств, сприяючи переходу від моделі виживання до моделі інноваційного відновлення та розвитку. /// EN: This article investigates the role of innovation as a strategic instrument for risk management and the strengthening of competitive advantages of Ukrainian industrial enterprises under conditions of uncertainty and wartime disruption. Using official statistical data for 2020–2024, the study examines the dynamics of innovation activity, the volume and structure of innovative product sales, and the sources of financing innovation. The research methodology is based on statistical analysis, comparison, and structural–dynamic assessment, which allowed identifying key phases of decline and recovery in industrial innovation development. The results demonstrate a pronounced decline in innovation activity during 2022–2023 as a consequence of military aggression, logistical disruptions, loss of production capacities, and heightened financial risks. However, 2024 marks the beginning of a recovery phase characterized by an increase in the number of innovation-active enterprises, substantial growth in innovative product sales, and diversification of innovation funding, including expanded participation of external investors. The findings confirm that innovation plays a decisive role in enhancing resilience, adaptability, and long-term competitiveness in the industrial sector. The study reveals the transition of enterprises from reactive survival strategies toward proactive innovation-driven development and market expansion. Innovation becomes not only a mechanism for technological modernization but also a core tool for reducing operational, market, and systemic risks and for supporting business continuity under crisis conditions. The scientific novelty of this study lies in the comprehensive assessment of innovation dynamics in the Ukrainian industrial sector during the wartime period and its transformation toward a recovery-driven model. The practical value of the results consists in offering evidence-based recommendations for enterprises and policymakers aimed at strengthening institutional support, improving investment mechanisms, and enhancing cooperation between business, government, and research institutions to accelerate post-war industrial recovery and ensure sustainable competitiveness.
Innovations as a tool for risk management and ensuring the competitive advantages of an enterprise
Keywords: інновації; управління ризиками; конкурентоспроможність; конкурентні переваги; інноваційна активність; стійкість; innovations; risk management; competitiveness; competitive advantages; innovation activity; resilience